Contribution of VSC-HVDC to Frequency Regulation of Power Systems With Offshore Wind Generation - Liu, Hongzhi; Chen, Zhe (IEEE transactions on energy conversion, 2015)
Modern large wind farms are required to provide frequency regulation service like conventional synchronous generation units. The frequency support capability of modern wind farms has been widely investigated and implemented. Remotely located large offshore wind farms are probably connected to the onshore system grid through voltage-source converter-based-high voltage direct current (VSC-HVdc) transmission systems. Due to the decoupling of VSC-HVdc and signal transmission delay, offshore wind farms may not be able to respond to the onshore grid frequency excursion in time and, consequently, the stability and security of the power system will be put at risk, especially for those with high wind penetration. This paper proposes a coordinated control scheme to allow VSC-HVdc link to contribute to the system frequency regulation by adjusting its dc-link voltage. By means of this approach, the dc capacitors of VSC-HVdc are controlled to absorb or release energy so as to provide frequency support. To further enhance the system frequency response, the frequency support from VSC-HVdc is also finely coordinated with that from offshore wind farm according to the latency of offshore wind farm responding to onshore grid frequency excursion. The control scheme is evaluated for both underfrequency and overfrequency events, and results are presented to demonstrate its effectiveness.